Using The Servqual Model To Assess Service Quality And Customer Satisfaction: An Empirical Study Of Rawang Rest Area - Vadovelu, Deepa (2014)
The purpose of this study is to analyze expected service, investigate perceived service and to analyze the effect of perceived service quality on the satisfaction level of Rawang rest area users. The results of this study would be beneficial to the new property developer who is going to be a new rest area in Rawang. Thus, to understand the perception and expectation of the Rawang RSA and Lay-by users a survey was conducted at the site. Questionnaire was distributed randomly to the willing users. The factors that were covered in the questionnaire were on the facilities, tangibility, responsiveness, reliability, assurance and empathy. There are many other factors that could affect the satisfaction level but basing on the reviewed literatures these factors were tested and adopted to be suitable for this study. From the analysis of this study it revealed that the expected service of the users were higher than the perceived service leading to low perceived service quality.